ZAKAT, INFAQ AND SHADAQAH (ZIS) DIGITALIZATION: A CASE STUDY USING TECHNOLOGY ORGANIZATION ENVIRONMENT FRAMEWORK - Frank Aligarh; Falikhatun Falikhatun; Arif Nugroho (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2023)
Technological disruption has changed the process of collecting zakat, infaq, and shodaqoh (ZIS). These changes can pose both threats and opportunities for ZIS institutions. This study aims to describe the acceptability of ZIS institutional technology from a Technology-Organization-Environment (TOE) perspective. This research is qualitative research with a case study approach. This study uses a data collection method consisting of observation, in-depth interviews, and documentation. Using in-person interviews and via cell phone. The subject of this research is the head of the ZIS institution. The results of the study state that all ZIS institutions have made technological innovations in collecting zakat, infaq, and shodaqoh. The existence of limited human resources and organizations' low acceptance of digital platforms are obstacles to not maximizing digital platforms' use. Strong encouragement from muzakki, government, and digital platform-based ZIS institutions has inspired them to develop technological innovations that suit their needs. This research contributes practically to ZIS institutions that the map of muzakki and donors has begun to change so that technological readiness is the key to the sustainability of ZIS institutions.